Culture Matters for Hanzi Learning Enjoyment and Hanzi Recognition: Evidence From Arabic Learners of Chinese as a Second/Foreign Language - Zhang, Haiwei; Yang, Shucheng (International Journal of Applied Linguistics, 2025)
ABSTRACT An increasing body of research has investigated the role of enjoyment in second language acquisition (SLA); however, few studies have explored whether learners of Chinese as a second/foreign language (CS/FL) experience enjoyment in learning Hanzi (Chinese characters) and how enjoyment impacts Hanzi recognition performance. To address this gap, a Hanzi Learning Enjoyment Scale was developed and administered to 446 Arabic CS/FL learners, 144 of whom also completed a Hanzi recognition test. Two key findings emerged. First, the results of factor analysis revealed four factors underlying Hanzi learning enjoyment: Hanzi culture, personal attitudes, teacher support, and personal fulfillment. Second, enjoyment did not emerge as a significant predictor of Hanzi recognition performance. Notably, the variance in Hanzi recognition scores explained by enjoyment ranked among the top three explanatory variables, comparable to the predictive power of years spent learning Chinese. This study concludes with theoretical insights into the construct of foreign language enjoyment (FLE) across different languages and language components, as well as practical recommendations for enhancing Hanzi instruction.
Keywords: Chinese as a second language; Chinese characters; foreign language enjoyment; Hanzi learning anxiety; Hanzi learning enjoyment; 外语学习愉悦感; 汉字习得; 汉字学习愉悦感; 汉字学习焦虑; 汉语二语学习